Importance of cardiac-synchronized vagus nerve stimulation parameters on the provoked chronotropic response for different levels of cardiac innervation - Haberbusch, Max; Kronsteiner, Bettina; Aigner, Philipp; Kiss, Attila; Podesser, Bruno Karl; Moscato, Francesco (Frontiers in Physiology, 2024)
Introduction. The influence of vagus nerve stimulation (VNS) parameters on provoked cardiac effects in different levels of cardiac innervation is not well understood yet. This study examines the effects of VNS on heart rate (HR) modulation across a spectrum of cardiac innervation states, providing data for the potential optimization of VNS in cardiac therapies. Materials and Methods. Utilizing previously published data from VNS experiments on six sheep with intact innervation, and data of additional experiments in five rabbits post bilateral rostral vagotomy, and four isolated rabbit hearts with removed sympathetic influences, the study explored the impact of diverse VNS parameters on HR. Results. Significant differences in physiological threshold charges were identified across groups: 0.09 ± 0.06 μC for intact, 0.20 ± 0.04 μC for vagotomized, and 9.00 ± 0.75 μC for isolated hearts. Charge was a key determinant of HR reduction across all innervation states, with diminishing correlations from intact (r = 0.7) to isolated hearts (r = 0.44). An inverse relationship was observed for the number of pulses, with its influence growing in conditions of reduced innervation (intact r=0.11, isolated r=0.37). Frequency and stimulation delay showed minimal correlations (r < 0.17) in all conditions. Conclusion. Our study highlights for the first time that VNS parameters, including stimulation intensity, pulse width, and pulse number, crucially modulate heart rate across different cardiac innervation states. Intensity and pulse width significantly influence heart rate in innervated states, while pulse number is key in denervated states. Frequency and delay have less impact impact across all innervation states. These findings suggest the importance of customizing VNS therapy based on innervation status, offering insights for optimizing cardiac neuromodulation.